11. Årbogen 2: Kvartsittbrudd fra eldre steinalder - Kvalheim, Alice Sunde (Tromura, 2025)
The activity at Årbogen 2 is associated with the utilization and collection of raw materials. The site is covered by moraine deposits left by the last Ice Age. These moraine deposits are rich in quartzite, which was exploited for various types of flaking technology at the site. The site mainly consists of localized find concentrations, containing typologically diverse categories of finds. The stone material indicates activity ranging from the Early Stone Age to the latter part of the Early Metal Age. The three C14 datings from the site support this, providing dates from 8100 BC to AD 802.